Número 13 (La Lupa. Colección fueguina de divulgación científica, 2018)
Comité EditorialAnna FranchTomás Ignacio MarinaVictoria Julieta GarcíaAdriana LasaValeria BartoliCatherine RoulierJulieta KaminskyUlises BalzaMaría GranittoNélida PalDiseño y DiagramaciónIrina Castro PeñaUshuaia, Tierra del Fuego, ArgentinaE-mail: iricastrop@gmail.comImpresiónM&A Diseño y Comunicación S.R.L.Buenos Aires, ArgentinaE-mail: info@myaweb.com.ar